ANALISIS PEMBAGIAN SISA HASIL USAHA BAGI ANGGOTA KOPERASI KARYAWAN HOTEL MARGA JAYA DI SAMARINDA TAHUN 2008-2012 - Eka Yudhyani & Abdul Rahmi (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
The purposes of this research is to analyse the division of Business Revenue Residue (BRR) of the Cooperative for Hotel Marga Jaya employee in Samarinda for year 2008-2012 which utilized the calculation techniques of Sitio and Tamba based on the members activities, which is from saving either from primary saving or obligatory saving, loan and purchase of things.